2018
DOI: 10.1007/s10815-018-1242-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-activated cell sorting of non-apoptotic spermatozoa improves the quality of embryos according to female age: a prospective sibling oocyte study

Abstract: Couples dealing with male infertility due to teratozoospermia can benefit from MACS selection of spermatozoa with higher percentage of good quality blastocysts but only when the woman is older than 30 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
(63 reference statements)
2
20
0
Order By: Relevance
“…These methods mostly include techniques such as intracytoplasmic morphologically selected sperm injection (IMSI), magnetic‐activated cell sorting (MACS) and physiologic intracytoplasmic sperm injection (PICSI). Although some promising preliminary results have been published regarding the use of these techniques (Dirican et al, ; Kim et al, ; Worrilow et al, ), recent reviews of the relevant clinical studies were insufficient to support their benefits in terms of clinical outcomes following IVF/ICSI (Avalos‐Duran et al, ; Stimpfel, Verdenik, Zorn, & Virant‐Klun, ; Teixeira et al, ). Also, the results of a recent preclinical study reported improved ICSI outcomes through sperm selection by thermotaxis in mice (Perez‐Cerezales et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These methods mostly include techniques such as intracytoplasmic morphologically selected sperm injection (IMSI), magnetic‐activated cell sorting (MACS) and physiologic intracytoplasmic sperm injection (PICSI). Although some promising preliminary results have been published regarding the use of these techniques (Dirican et al, ; Kim et al, ; Worrilow et al, ), recent reviews of the relevant clinical studies were insufficient to support their benefits in terms of clinical outcomes following IVF/ICSI (Avalos‐Duran et al, ; Stimpfel, Verdenik, Zorn, & Virant‐Klun, ; Teixeira et al, ). Also, the results of a recent preclinical study reported improved ICSI outcomes through sperm selection by thermotaxis in mice (Perez‐Cerezales et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen women underwent a short antagonist and five women a long agonist protocol of ovarian hyperstimulation. Both protocols were conducted as described previously 24 . The short protocol was started on day 2 of the menstrual cycle with a daily starting dose of 200‐225 IU of recombinant FSH (Gonal F, Merck Serono).…”
Section: Methodsmentioning
confidence: 99%
“…On the day of oocyte aspiration, the preparation of sperm samples and MACS of non‐apoptotic spermatozoa was performed as described previously 24 . Briefly, after obtaining the samples, they were assessed for volume, concentration, motility, and morphology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, sperm preparation methods such as DGC and swim up could separate motile spermatozoa with normal morphology, but recently, several sperm preparation procedures have been developed based on cellular and molecular characteristics (Nasr‐Esfahani, Deemeh, & Tavalaee, ; Rappa et al, ) including surface marker (Magnetic Activated Cell Sorting) (Stimpfel, Verdenik, Zorn, & Virant‐Klun, ; Ziarati, Tavalaee, Bahadorani, & Nasr Esfahani, ), surface receptors (hyaluronic acid binding receptors) (Jakab et al, ; Nasr‐Esfahani, Razavi, Javdan et al, ; Nasr‐Esfahani, Razavi, Vahdati et al, ) and sperm membrane electric charge (Zeta potential) (Chan, Jacobson, Corselli, & Patton, ). Sperm membrane contains proteins and glycoprotein inserted in a fluid lipid bilayer and plays a dynamic role in spermatozoa–oocyte cross‐talk and fertilisation.…”
Section: Introductionmentioning
confidence: 99%